Old Beijing, New Life - Huang, Haiyang; Zhang, Wei; Wang, Menghua (MAJ - Malaysia Architectural Journal, 2025)
The hutong or courtyard house is the typical form of settlement in Beijing and forms the historical context of this culturally rich city. However, in the process of urbanization, massive population growth has led to disorderly and chaotic construction constructions, resulting in the collapse of the traditional spatial order and a rapid deterioration in the quality of life. The Xizongbu District is located 1.4 kilometers east of the Forbidden City. As one of the traditional Hutong districts, it shares similar problems: Residents' living spaces are overcrowded and lack sufficient sunlight; a large number of self-built houses have poor infrastructure and high structural risk; community services and quality communal places are absent; the transport network is imperfect in the face of high urban density, with many dead ends; there is little public space in the narrow hutongs, so children have to compete with motor vehicles for use of the roads. In this situation, many occupants constantly left, yet many more have no choice but stay. However, due to high land costs and political restrictions, the living environment is impossible to be improved by either the government or residents. To break this deadlock, the design team worked with the local CDC (community development company) to jointly intervene in the renovation and regeneration of this area, aiming to restore harmony and dignity to everyday life and ultimately revitalise communities.